Educational Physical Activity Program Using Audio-Visual Media and Sports Assistance for Pregnant Women in Sudimara Village, Banyumas Regency - Dede, Jajang; Rifqi Festiawan; Aisyah Apriliciciliana Aryani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The community service project addressed the main issue of insufficient understanding of healthy physical activity and lack of exercise guidance for pregnant women in the community of Sudimara Village, Banyumas Regency. The primary objective was to enhance knowledge and increase physical activity among pregnant women. The methods used included education through audio-visual media, assistance with pregnancy exercise routines, and follow-up activities to ensure the sustainability of these practices. The results showed a significant improvement in the knowledge and attitudes of pregnant women after receiving the education. However, there were also hindering factors such as limited time and available resources, and some participants experienced a decline in attitude despite the education provided.